Perspective: a review of lifecycle management research on complex products in smart-connected environments. Issue 21 (2nd November 2019) - Zhang, Qiang; Lu, Xiaonong; Peng, Zhanglin; Ren, Minglun
Abstract : Smart-connected technologies, such as the Internet of things and cloud computing, are transforming how industries and enterprises do business by improving the lifecycle management of their product. Therefore, to study the lifecycle management of complex products under smart-connected environment, many studies have been published outlining new methods for smart development, intelligent manufacturing, and data-driven services. This paper first proposes the concept and architecture of smart-connected products and then systematically reviews the current research about new paradigms of product development, manufacturing and services. The paper also summarises the conceptual framework, research issues and opportunities of each phase of the product lifecycle management.